The Armorican Quartzite: when trilobites ruled the Ordovician seas of the Villuercas-Ibores-Jara UNESCO Global Geopark, Spain - Ivan Cortijo; Sören Jensen; Manolo Garcia; Teodoro Palacios; José María Barrera (Geoconservation Research)
Cruziana is a common and widespread trace fossil in Lower Palaeozoic strata that is generally attributed to the activity of trilobites. The Lower to Middle Ordovician Armorican Quartzite Formation of southern Europe contains well-preserved examples of the Cruziana rugosa Group. This paper outlines how Cruziana forms an important part of the geological heritage in the Villuercas-Ibores-Jara UNESCO Global Geopark, Cáceres Province (SW Spain).